From Concept to Practice, Establishing Clinical Trials Unit at PKLI&RC in a Resource-Limited Setting - Sadia Hassan (PKLI Journal of Health Sciences, 2026)
Clinical trials are widely considered as gold standard research studies for evidence-based decision making in healthcare practices. Clinical trials, however, are quite expensive, time consuming and involve a wide range of complex and closely monitored operations including regulatory approvals, initial screening, subject accrual, data collection interpretation and dissemination of results. Conducting clinical trials in low-middle income countries with resource limiting settings adds to this complexity.